Improvement of Informational and Analytical Base of Development of Russia’s Fuel and Energy Companies in the Sphere of Energy Saving and Energy Efficiency - Kreydenko, Tatiana; Chernyaev, Maxim; Grigorieva, Elena; Korenevskaya, Anna (International Journal of Energy Economics and Policy, 2020)
The article is devoted to the analysis of the questions of the development of the mechanism of forming of Russia’s fuel & energy companies’ policy in the sphere of energy saving and energy efficiency increase based on improving the informational and analytical base of a company’s activity efficiency level assessment. The events’ implementation effectiveness of the corporate policy in the sphere of energy efficiency depends, first of all, on the optimal combination of the tools applied. The fundamental processes of high-quality enterprise management in these conditions could be developing and improving the key indicators of the reached energy efficiency level of a company and its monitoring that should cover all the aspects of stable development. In the article, there are suggested and tested the authorial methodology of the energy efficiency level assessment of fuel-and-energy companies with the example of the leading oil and gas companies using the financial and non-financial statements reports (in accordance with the international report composing standards). Keywords: energy efficiency, fuel and energy complex, oil and gas industry, energy efficiency indicators, energy efficiency increasing tools. JEL Classifications: Q40, Q43, Q48. DOI: https://doi.org/10.32479/ijeep.9083